2015
DOI: 10.1093/eurheartj/ehv501
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antiarrhythmic Drugs Short-Term Use After Catheter Ablation for Atrial Fibrillation (EAST-AF) trial

Abstract: Short-term use of AAD for 90 days following AF ablation reduced the incidence of recurrent atrial tachyarrhythmias during the treatment period, but it did not lead to improved clinical outcomes at the later phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 26 publications
4
80
3
8
Order By: Relevance
“…21 U navedenom je Atrial Fibrillation trial, a total of 2038 patients were randomly assigned to antiarrhythmic drug therapy of control following radiofrequency catheter ablation for paroxysmal, persistent, or long-lasting AF. 16 The risk of recurrent atrial tachyarrhythmias was reduced in the antiarrhytmic drug therapy group during the treatment period of 3 months, however without an effect on clinical outcomes at later time points. …”
Section: Prevencija Moždanog Udaramentioning
confidence: 87%
See 1 more Smart Citation
“…21 U navedenom je Atrial Fibrillation trial, a total of 2038 patients were randomly assigned to antiarrhythmic drug therapy of control following radiofrequency catheter ablation for paroxysmal, persistent, or long-lasting AF. 16 The risk of recurrent atrial tachyarrhythmias was reduced in the antiarrhytmic drug therapy group during the treatment period of 3 months, however without an effect on clinical outcomes at later time points. …”
Section: Prevencija Moždanog Udaramentioning
confidence: 87%
“…U ispitivanju Efficacy of Antiarrhythmic Drugs Short-Term Use After Catheter Ablation for Atrial Fibrillation ukupno je 2038 ispitanika nasumično randomizirano za primjenu antiaritmijskih lijekova za kontrolu FA-a nakon RF kateterske ablacije paroksizmalne, perzistentne i dugotrajne FA. 16 Rizik od recidiva atrijske tahiaritmije bio je manji u grupi s antiaritmijskim lijekovima tijekom razdoblja praćenja od 3 mjeseca, ali bez učinka na klinički ishod u kasnijem tijeku.…”
unclassified
“…In two of the trials included [10,13,14,[17][18][19][20][21][22][23], (both of amiodarone) there are data concerning percentage of time patients were in sinus rhythm during drug exposure. In Darkner et al [13], the amiodarone group showed significantly lower rate of atrial tachyarrhythmia-related hospitalizations [rate ratio = 0.43; 95 % confidence interval (CI) = 0.23-0.77, P = 0.006] and cardioversions (rate ratio = 0.36; 95 % CI = 0.20-0.62, P = 0.0004) within the period of drug administration .In Kaitani et al [17], patients assigned to AAD had a significantly lower rate of atrial tachyarrhythmias recurrence compared to the control group during the 90-day treatment period [59.0 and 52.1 %, respectively; adjusted hazard ratio (HR) 0.84; 95 % confidence interval (CI) 0.73-0.96; P = 0.01].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive analysis excluding Kaitani et al [17] during posttreatment follow-up, the overall recurrence of arrhythmia rate was 31.4 % in the AAD group vs. 38.08 % in control patients (odd ratio 0.79, 95 % CI 0.58-1.09, P = 0.15) (Fig. 4).…”
Section: Summary Of the Studies And Baseline Characteristics Of Patientsmentioning
confidence: 93%
See 1 more Smart Citation